The missing - Mooney, Chris (London : Penguin Books, 2007)
Darby McCormick had known Melanie Cruz and Stacey Stephens forever. Best friends since childhood, the threesome had survived high school together. But one night in the woods, drinking beers to celebrate Melanie's sixteenth birthday, the three unsuspecting teenagers witnessed the grisly murder of a woman. Darby and her friends fled the scene, but they left behind a clue to their whereabouts, which only simplified the killer's revenge. It didn't take long to find them. This time, only Darby survived.Twenty-five years later, Darby is a crime-scene investigator for the Boston Police Department. When a young woman is abducted from her home in the middle of the night, Darby finds an unexpected witness -- a woman dressed in rags hiding behind garbage cans kept underneath the back porch of the victim's house. The woman is dangerously malnourished and is so distraught, so terrified, she believes she is still locked inside a dark prison cell -- and that Darby is one of her fellow prisoners.Darby's investigation reveals that the woman, Rachel Swanson, has been missing for more than five years. And there are others. As Darby tries to get Rachel to talk about the other missing women and the horrors she endured, the killer known as Traveler is brought to light. As the race to find him heats up, Darby finds herself trying to unravel forensic clues about the case while attempting to uncover the existence of a killer who has eluded the police and FBI for more than two decades. A killer who, years ago, introduced Darby to violence and death. A killer who will use every means necessary to protect himself and to keep the missing women from ever being found. A breathless, gripping read from beginning to end, The Missing is an unforgettable story about a courageous woman whose past has literally come back to haunt her. Told with tremendous style at a breakneck pace, this is thriller writing at its best.